Study on the relationship between psychological status and sports habits of Law College Students - Lu Zhang; Lin Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This study aims to examine the relationship between psychological status and exercise habits of law college students. This study used literature to develop a theoretical foundation, and a questionnaire survey was carried out for data collection. Furthermore, this study used a statistical tool to analyse the collected data. Thus, this study investigated the relationship between college students' mental health and physical exercise by using a survey. Students majoring in law colleges mainly participate in physical exercise 2 ~ 3 times a week. Most college students exercise between 16 and 45 minutes each time. The physical exercise load of college students is mainly of medium intensity. The main factors affecting college students' participation in physical exercise are insufficient stadiums, no time and no organisation. Physical exercise is closely related to college students' mental health. Long-term physical activity is conducive to improving College Students' mental health levels.